2020
DOI: 10.3390/f11121259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Abiotic Controls on Windthrow Disturbance Using a Generalized Additive Model: A Case Study of the Tatra National Park, Slovakia

Abstract: Windthrows are the most important type of disturbance occurring in the forests of Central Europe. On 19 November 2004, the strong northeastern katabatic winds caused significant damage and land cover change to more than 126 km2 of spruce forests in the Tatra National Park. The risk of subsequent soil erosion and accelerated runoff has increased in the affected habitats. Similar situations may reoccur this century as a consequence of climate change. A geographical approach and detailed research of the damaged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…More than 126 km 2 of forests were damaged, with a wood volume of 2.3 million m 3 located at altitudes between 700 and 1350 m. The wind caused widespread damage, and it even contributed to the death of one person. 84,000 cubic meters of timber had to be removed from the intra-urban areas of various Tatra settlements [4].…”
Section: Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 126 km 2 of forests were damaged, with a wood volume of 2.3 million m 3 located at altitudes between 700 and 1350 m. The wind caused widespread damage, and it even contributed to the death of one person. 84,000 cubic meters of timber had to be removed from the intra-urban areas of various Tatra settlements [4].…”
Section: Study Areasmentioning
confidence: 99%
“…Research of spruce stands wind disturbances in Central Europe identified the age of stands, higher percentages of spruce, georelief and soils as the most important factors influencing the degree of forest damage [3]. A detailed evaluation of abiotic controls on windthrow disturbances in Tatras was carried out by Falt'an et al [4]. conservation priorities from a systemic ecoregional approach [22].…”
Section: Introductionmentioning
confidence: 99%
“…Strong winds breaking or uprooting trees are one of the most important abiotic factors with a huge impact on the initiation of changes in vegetation [1,2]. They are the main cause of live biomass loss in northern European forests [3].…”
Section: Introductionmentioning
confidence: 99%
“…Wind disturbance has been studied in temperate forest ecosystems, especially in North America [11][12][13][14]. Studies in Eastern Europe investigating this problem have focused mainly on mountain forests and poor habitats that cover the largest areas [2,7,[15][16][17][18][19][20]. Studies investigating long-term transformations caused by windstorms are gaining a new meaning in the light of climate change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation